Evaluasi Koordinasi Ocr Dan Gfr Di Gardu Induk Distribusi - Rezky Almi Ramadhan; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
An electric power system must have reliable and continuously supply the need for electrical energy. One of methods to support reliability is a protection system that can handle the fault. Fault on the distribution network is short circuit fault, if it not removed immediately it will damage the equipment in its path. Protection relays commonly used on distribution networks to protect the system from short circuit fault are Over Current Relay (OCR) and Ground Fault Relay (GFR) to maintain and improve the distribution networks protection system it is necessary to evaluate the coordination of the installed relay. The protection relay coordination is when short circuit fault appear in the system , the closest relay point to the fault point will work and gives a signal to trip the circuit breaker When a short circuit fault occurs, the relay closest to the fault point will work first and if the fault current value exceeds the adjustment of the backup relay behind it, the backup relay will trip after the main relay trip. When checked, time grading on the installed conditions does not meet the IEC 60255 standard, which is 0.4-0.5 seconds. So, the adjustment is done and the time grading between OCR is obtained according to IEC 60255 standard, which is 0.402 seconds. While the GFR in the installed condition also does not meet with the IEC 60255 standard so the adjustment is performed and the evaluation time between the GFR in accordance with the IEC 60255 standard is 0.492 seconds. Keywords: GFR, Protection system, OCR